Identifikasi Senyawa Sibutramin Hidroklorida Pada Jamu Pelangsing - Fakhriah, Siti Nurintan; Rahmadani, Rahmadani; Mahdiyah, Dede (Jurnal Farmasi & Sains Indonesia, 2022)
Dissatisfaction with the current body causes women to try to change their appearance by losing weight quickly which results in switching to slimming herbal products that can be trusted to lose weight instantly. With the current progress in the circulation of slimming herbal products, medicinal chemicals (BKO) are added. Slimming herbal products are prohibited from containing medicinal chemicals. Sibutramine Hydrochloride is one of the BKOs found in slimming herbs because Sibutramine HCl is a hard drug that works by inhibiting norepinephrine, serotonin and dopamine, which can suppress appetite so it can be used to lose weight. The study was conducted to identify the compound Sibutramine Hydrochloride in slimming herbs circulating in Tanah Grogot. The method used is pre-experimental with one shot case study. Sampling was done by purvosive sampling technique. The sample from the study was 10 slimming herbs circulating in Tanah Grogot. The results of the TLC method identified 10 samples, only 1 sample was positive for Sibutramine HCl because it had the same Rf value as the comparison standard, which was 0.95. The UV-Vis Spectrophotometry method obtained the sample results showing the levels of Sibutramine HCl exceeding the dose of 15mg with the sample content containing % Sibutramine HCl content, namely S4 0.59%. The results of this study are that there are slimming herbs with a BPOM permit that contain the medicinal chemical Sibutramine HCl.